Classificação de risco para internação hospitalar em idosos institucionalizados de Botucatu-SP - Galvão, André Augusto. [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The aging process is a naturally continuous physiological process. The Long Stay Institutions are shared houses for people who are aged sixty or older. People in this age group have hospitalization rate three times higher than regular and hospitalization generates immobility and functional decline. Boult developed a Rapid Risk Screening questionnaire where the risk for future hospitalization can be identified. Objective: Evaluate the institutionalized elderly regarding the risk of future hospitalizations. Methodology: An exploratory and descriptive cross-sectional study to be carried out from October 2018 until February 2019, with institutionalized elderly people at the Long Stay Institutions. A structured script containing sociodemographic information will be used followed by the use of the Rapid Risk Screening instrument. The elderly will be classified as low (0), medium (1), medium-high (2) or high (3). The project was approved by the Research Ethics Committee of FMB-UNESP (CAAE: 98376918.5.0000.5411 - nº 2,932,001). Results: 63 elderly people were evaluated, 55.6% (35) female. The mean age (+ dp) of the elderly was 77.2 (+ 8.9), 19% of the elderly reported having Coronary Artery Disease and 31.7%, Diabetes Mellitus. They had 100% social support. They had 49.2% hospital stay and 74.6% were consulted in the last six months. Regarding health perception, 42 (66.6%) reported poor or average health. When the risk for hospitalization was evaluated, it was verified that 77.8% of the elderly had a high probability. Discussion: Regarding the risk for hospitalization, it was observed that 96.8% of the population in the study presented a medium to high probability of hospitalization risk. Using the same instrument and comparing the results from the study with the elderly in the community of Botucatu, regarding the risk of hospitalization, a lower value of 43.6% could be observed. It is important to emphasize that the elderly were from different situations, since they were not institutionalized. It should be pointed out that the present study was carried out with the elderly institutionalized in a Long Stay Institutions, such a risk stratum is shown to be important in relation to similar institutions in general, due to its considered high risk for hospital admission. Conclusion: In the course of this study, it was possible to identify that the risk of hospital admission is related to several factors, where the Rapid Risk Screening, a questionnaire with easy access and application, with several variables, presents results that are directly correlated with the risk of the elderly hospitalized.

Envelhecer é um processo fisiológico de curso natural. As Instituições de Longa Permanência (ILPIs) configuram-se um domicilio coletivo para pessoas que tenha idade igual ou superior a sessenta anos, pessoas nessa faixa etárias, têm um índice de internação três vezes maior e a hospitalização gera imobilidade e declínio funcional. Boult desenvolveu um questionário de Triagem Rápida de Risco (TRR) onde pode ser identificado o risco para futura hospitalização. Objetivo: Avaliar os idosos institucionalizados quanto ao risco de futuras hospitalizações. Metodologia: Estudo exploratório e descritivo, de corte transversal, a ser realizado no período de outubro de 2018 a fevereiro de 2019, com idosos institucionalizados na ILPI. Será utilizado roteiro estruturado contendo informações sociodemográficas e em seguida será utilizado o instrumento de TRR. Os idosos avaliados serão classificados quanto ao risco de internação em: baixo (0), médio (1), médio-alto (2) ou alto (3). O projeto foi aprovado pelo Comitê de Ética em Pesquisa da FMB-UNESP (CAAE: 98376918.5.0000.5411 – nº 2.932.001). Resultados: Formam avaliados 63 idosos, sendo 55,6% (35) feminino. A média de idade (+ dp) dos idosos foi de 77,2 (+ 8,9), 19% dos idosos referiram ter Doença Arterial Coronariana e 31,7%, Diabetes Mellitus. Possuíam suporte social 100%. Tiveram pernoite hospitalar 49,2% e foram consultados nos últimos seis meses 74,6%. Quanto à percepção de saúde, 42 (66,6%) referiam saúde péssima ou média. Quando avaliado o risco para internações, verificou-se que 77,8% dos idosos apresentavam alta probabilidade. Discussão: Em relação ao risco para internação, observou-se que 96,8% da população estudada apresentou de média a alta probabilidade de risco de internação. Ao comparar aos resultados de estudo com idosos da comunidade de Botucatu, este obteve valor menor, de 43,6% quanto ao risco de internação, utilizando o mesmo instrumento. É importante ressaltar que os idosos eram de situações distintas, pois os mesmos não estavam institucionalizados. Salienta-se que o presente estudo foi realizado com idosos institucionalizados em uma ILPI, tal estrato de risco demonstra-se importante perante demais instituições semelhantes de um modo geral, devido ao seu resultado considerado alto para risco de internação hospitalar. Conclusão: Ao decorrer desse estudo, foi possível identificar que o risco de internação hospitalar está relacionado a vários fatores, onde o TRR, um questionário de fácil acesso e aplicação, dotado de diversas variáveis, apresenta resultados que estão correlacionados diretamente com o risco do idoso vir a ser hospitalizado.
Keywords: Comprehensive geriatric assessment; Older people; Long term care facilities; Avaliação geriátrica ampla; Idoso; Instituição de longa permanência